ANALISIS KINERJA REKSA DANA SAHAM MENGGUNAKAN METODE SHARPE,TREYNOR DAN JENSEN - , Tonggo M. Simanjuntak, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Mutual Fund is one of developing investment instrument which goes simultaneously with Indonesian capital market growth. Sharia fund was made to accommodate various societies investment demand and objectives. Sharia fund is generally similar with conventional mutual funds. It is categorized as an open mutual fund in a form of Collective Investment Contract (CIC). The fundamental difference between conventional mutual fund and sharia fund is on their investment policy. Sharia fundâs investment policies, including portfolio selection and its management strategy, have been adjusted to accord with the Islamic principle. Mutual fund performance measurement (especially for sharia fund) is an essential stage which must be done by investors before they invest in that instrument. One of the indicators to evaluate sharia fund performance is the successfulness of fund managers strategy in managing sharia funds portfolio. It is normally reflected from its Net Asset Value (NAV). This research evaluates sharia equity funds performances (by comparing daily NAV and its daily market return (Jakarta Islamic Index)) and conventional equity funds performances (by comparing its daily NAV and IDX Composite Price Index) using Sharpe Method (RVAR), Treynor Method (RVOL) and Jensen Method (ALPHA). RVAR measures portfolio performance using total risk or deviation standard as risk indicator. RVOL and ALPHA use systemic risks or beta as risk indicator. Higher RVAR,RVOL, and ALPHA scores of a fund indicates a better performance. Sharia funds performances in 2009 is generally good compare to conventional funds performances, as shown in the first position of its Treynor, Sharpe and Jensen